Clinical and histopathologic features of antibody‐mediated rejection among pediatric renal transplant recipients with preformed vs de novo donor‐specific antibodies. (20th November 2017) - Steggerda, Justin A.; Kim, Irene K.; Haas, Mark; Zhang, Xiaohai; Kang, Alexis; Pizzo, Helen; Kamil, Elaine; Jordan, Stanley; Puliyanda, Dechu
Abstract: Preformed and de novo donor specific antibodies (pDSA and dnDSA) are risk factors for ABMR. This study compares the effects of pDSA vs dnDSA in pediatric kidney transplant recipients. Sixteen pediatric patients with biopsy‐proven ABMR were evaluated. Strong DSA (MFI >10 000) was recorded at transplant, rejection, and follow‐up. DSAs with the highest MFI were termed iDSAs. Allograft biopsies were scored according to Banff 2013 criteria. Seven of 16 (44%) patients had pDSA at transplant; 9 (56%) developed dnDSA. Patients with pDSA developed ABMR earlier (median = 63 vs 1344 days, P  = .017), while patients with dnDSA were more likely to have strong Class II iDSA (100% vs 28%, P  = .009). Viral infection or non‐adherence was more common in patients developing dnDSA (88.8% vs 28.6%, P  < .01). Pathology in those with pDSAs demonstrated worse transplant glomerulitis (g score 1.57 ± 0.98 vs 0.56 ± 0.73, P  = .031); however, those with dnDSAs exhibited higher C4d+ ABMR ( P  = .013). Patients developing dnDSAs showed ABMR later post‐transplant with predominance of HLA‐Class II iDSAs. Inadequate immunosuppression likely contributes to dnDSA formation. Patients with no DSA who have unprotocolized decreases in immunosuppression should be screened for dnDSA as it could lead to early intervention and potentially better outcomes.